Are Older Adults Willing to Consider New Strategies to Reduce Stroke Risk?. (March 2019) - Grande, Stuart W.; O'Neill, Elizabeth S.; Sherman, Ariel E.; Coylewright, Megan
Atrial fibrillation (AF) is a common arrhythmia that increases patients' risk of stroke, and determining an optimal prevention therapy is a preference-sensitive decision appropriate for shared decision making (SDM). Utilizing community-based focus groups, we explored beliefs and values around options for stroke prevention. Interview transcripts from five independent focus groups were qualitatively assessed and organized into themes. Most participants were taking a blood thinner (93%) and more than half of participants (64%) reported having AF. Few participants were familiar with newer therapies. Qualitative analysis revealed three themes: (a) fearing loss of self-control through debilitating stroke, (b) recognizing uncertainty in how to weigh risks and benefits of new treatments, and (c) needing mutual respect between clinicians and patients to consider new/alternative treatment regimens. These findings help direct future research efforts examining optimal timing for SDM and decision aids to promote mutual respect.